Clinical characteristics and visual outcome, prognostic factor, visual acuity and globe survival in posterior segment intraocular foreign body at Tilganga Institute of Ophthalmology - Sharma, Sanjita; Thapa, Raba; Bajimaya, Sanyam; Pradhan, Eli; Poudyal, Govinda (Nepalese Journal of Ophthalmology, 2018)
Purpose: To evaluate clinical characteristics, visual outcomes and globe survival after intraocular foreign body removal from posterior segment via pars plana approach. Methods: A hospital based retrospective study. All the patients of penetrating eye injury with intraocular foreign body in posterior segment as detected by computed tomography were enrolled from 2012 to 2014. Results: Thirty patients of 30 eyes were included. The mean age was 27.7 years. (2-52). Twenty-four (80%) were male. Out of 30 eyes 19 (63.3%) eyes had injury at Zone 1 and 11 (36.7%) eyes had injury at Zone 2. The mean time spent between primary repair following surgery and intra ocular foreign body removal, was 15.47 days. Retinal detachment and endophthalmitis prior to intraocular foreign body removal was present in 9/30 of eyes. We looked for correlation between post operative Phthisis bulbi with zone of injury and pre operative endophthalmitis and preoperative retinal detachment. However, p value for the above correlation was more than 0.552 and 0.815 respectively, which was statistically not significant. Conclusions: The eyes with posterior segment intraocular foreign bodies showing clinical features of preoperative endophthalmitis, retinal detachment and the zone of injury also did not have any direct significance with globe survival.